Factors associated with foreign body infection in methicillin-resistant Staphylococcus aureus bacteremia - Bouiller, Kevin; Jacko, Natasia F.; Shumaker, Margot J.; Talbot, Brooke M.; Read, Timothy D.; David, Michael Z. (Frontiers in Immunology, 2024)
Background We aimed to compare patient characteristics, MRSA sequence types, and biofilm production of MRSA strains that did and did not cause a foreign body infection in patients with MRSA bloodstream infections (BSI) Methods All adult patients with MRSA BSI hospitalized in two hospitals were identified by clinical microbiology laboratory surveillance. Only patients who had at least one implanted foreign body during the episode of BSI were included. Results In July 2018 - March 2022, of 423 patients identified with MRSA BSI, 118 (28%) had ≥1 foreign body. Among them, 51 (43%) had one or more foreign body infections. In multivariable analysis, factors associated with foreign body infection were history of MRSA infection in the last year (OR=4.7 [1.4-15.5], p=0.012) community-associated BSI (OR=68.1 [4.2-1114.3], p=0.003); surgical site infection as source of infection (OR=11.8 [2-70.4], p=0.007); presence of more than one foreign body (OR=3.4 [1.1-10.7], p=0.033); interval between foreign body implantation and infection <18 months (OR=3.3 [1.1-10], p=0.031); and positive blood culture ≥48h (OR=16.7 [4.3-65.7], p<0.001). The most prevalent sequence type was ST8 (39%), followed by ST5 (29%), and ST105 (20%) with no significant difference between patients with or without foreign body infection. Only 39% of MRSA isolates formed a moderate/strong biofilm. No significant difference was observed between patients with foreign body infection and those without foreign body infection. In multivariable analysis, subjects infected with a MRSA isolate producing moderate/strong in vitro biofilm were more likely to have a history of MRSA infection in the last year (OR=3.41 [1.23-9.43]), interval between foreign body implantation and MRSA BSI <18 months (OR=3.1 [1.05-9.2]) and ST8 (OR=10.64 [2-57.3]). Conclusion Most factors associated with foreign body infection in MRSA BSI were also characteristic of persistent infections. Biofilm-forming isolates were not associated with a higher risk of foreign-body infection but appeared to be associated with MRSA genetic lineage, especially ST8.